Effect of Praziquantel Treatment during Pregnancy on Cytokine Responses to Schistosome Antigens: Results of a Randomized, Placebo-Controlled Trial - Tweyongyere, Robert; Mawa, Patrice A.; Ngom-wegi, Sophy; Ndibazza, Juliet; Duong, Trinh; Vennervald, Birgitte J.; Dunne, David W.; Katunguka-Rwakishaya, Eli; Elliott, Alison M. (The Journal of infectious diseases, 2008)
Praziquantel treatment of schistosomiasis boosts antischistosome responses, with type 2 helper T cell bias that may contribute to immunologically mediated killing and to protection against reinfection. Praziquantel treatment during pregnancy was recommended in 2002, but the immunological effects of the treatment had not been investigated.A cohort of 387 Schistosoma mansoni-infected women were recruited from a larger trial of deworming during pregnancy. Women were randomized to receive either praziquantel or placebo during pregnancy. Six weeks after delivery, all women received praziquantel. Cytokine responses to S. mansoni worm and egg antigens were measured in whole blood culture before and 6 weeks after each treatment.Schistosome-specific cytokine responses were suppressed during pregnancy. Praziquantel treatment during pregnancy caused significant boosts in interferon-γ (IFN-γ), interleukin (IL)-2, IL-4, IL-5, IL-13, and IL-10 responses to schistosome worm antigen and in IFN-γ, IL-5, and IL-13 responses to schistosome egg antigen, but these boosts were not as substantial as those seen for women treated after delivery.Pregnancy suppresses a potentially beneficial boost in cytokine responses associated with praziquantel treatment. Further studies are needed on the long-term effects that treatment of schistosomiasis during pregnancy have on morbidity and resistance to reinfection among treated women and their offspring.
Keywords: cytokine; pregnancy; antigens; interleukin-10; interleukin-13; interleukin-4; interleukin-5; praziquantel; schistosoma; schistosomatidae; schistosomiasis; helminths